2007
DOI: 10.1093/ajcn/85.1.102
|View full text |Cite
|
Sign up to set email alerts
|

FABP2 Ala54Thr genotype is associated with glucoregulatory function and lipid oxidation after a high-fat meal in sedentary nondiabetic men and women

Abstract: In sedentary nondiabetic persons following a low-fat diet, FABP2 Thr54 carriers have lower glucose tolerance and lower insulin action than do Ala54-homozygous persons. Furthermore, FABP Thr54 carriers have higher lipid oxidation rates, which may be the mechanism of glucoregulatory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
3
33
0
2
Order By: Relevance
“…Carriers of the Thr54 allele have less peripheral insulin sensitivity after the intake of a SFA diet than after the intake of an olive oil-rich diet. Weiss et al [10] have reported that in sedentary nondiabetic persons following a low-fat diet, FABP2 Thr54 carriers have lower glucose tolerance and lower insulin action than Ala54-homozygous persons. Our group had demonstrated that weight loss, after a short-term intervention of 2 months, is associated with different biochemical changes depending of FABP2 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carriers of the Thr54 allele have less peripheral insulin sensitivity after the intake of a SFA diet than after the intake of an olive oil-rich diet. Weiss et al [10] have reported that in sedentary nondiabetic persons following a low-fat diet, FABP2 Thr54 carriers have lower glucose tolerance and lower insulin action than Ala54-homozygous persons. Our group had demonstrated that weight loss, after a short-term intervention of 2 months, is associated with different biochemical changes depending of FABP2 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of Thr54-containing protein have a different response secondary to a standard hypocaloric diet than wild type obese [9] with a better lipid response in non-Thr carriers. Other studies [10] have demonstrated that in nondiabetic obese subjects following a low-fat diet and a low-carbohydrate diet, FABP Ala-54 homozygous had a better insulin improvement and lipid modification than Thr54-carriers. The distribution of dietary fat in hypocaloric diet could have a role in the metabolic response secondary to weight loss with this polymorphism [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…8 In the glucose-fatty acid cycle, enhanced lipid oxidation would impair glucose utilization, which might influence the blood glucose level and, consequently, food appetite. The differences in glucoregulatory function and lipid oxidation might be partly explained by the genotype-dependent eating behavior.…”
mentioning
confidence: 99%
“…6 Many, but not all, association studies on this variation in insulin resistance and fasting, or postprandial blood glucose and triglyceride levels have identified a relationship between genotypes and phenotypes. 7,8 In this study, we tested the hypothesis that the FABP2 gene polymorphism is associated with food consumption and nutritional intake.…”
mentioning
confidence: 99%
“…5 Thr54 carriers also show higher lipid oxidation rates, which might prevent an excessive increase in fasting and postprandial lipids. 8 In the glucose-fatty acid cycle, enhanced lipid oxidation would impair glucose utilization, which might influence the blood glucose level and, consequently, food appetite. The differences in glucoregulatory function and lipid oxidation might be partly explained by the genotype-dependent eating behavior.…”
mentioning
confidence: 99%